Comprehensive analysis of REST corepressors (RCORs) in pan-cancer - Zheng, Rong; Pan, Yingying; Liu, Xinhui; Liu, Feiye; Li, Aimin; Zheng, Dayong; Luo, Yue (Frontiers in Cell and Developmental Biology, 2023)
REST corepressors (RCORs) are the core component of the LSD1/CoREST/HDACs transcriptional repressor complex, which have been revealed differently expressed in various cancers, but the therapeutic and prognostic mechanisms in cancer are still poorly understood. In this study, we analyzed expression, prognostic value, molecular subtypes, genetic alteration, immunotherapy response and drug sensitivity of RCORs in pan-cancer. Clinical correlation, stemness index, immune infiltration and regulatory networks of RCORs in hepatocellular carcinoma (HCC) were detected through TCGA and GSCA database. In-vitro experiments were conducted to explore the role of RCOR1 in HCC cells. The expression of RCORs varied among different cancers, and have prognostic values in several cancers. Cancer subtypes were categorized according to the expression of RCORs with clinical information. RCORs were significantly correlated with immunotherapy response, MSI, drug sensitivity and genetic alteration in pan-cancer. In HCC, RCORs were considered as potential predictor of stemness and also had association with immune infiltration. The ceRNA-TF-kinase regulatory networks of RCORs were constructed. Besides, RCOR1 acts as an oncogene in HCC and promotes the proliferation of HCC cells by inhibiting cell cycle arrest and cell apoptosis. Taken together, our study revealed the potential molecular mechanisms of RCORs in pan-cancer, offering a benchmark for disease-related research.